PENGGUNAAN KENDARAAN PRIBADI YANG DIGUNAKAN SEBAGAI ANGKUTAN UMUM PENUMPANG ATAU BARANG DI KABUPATEN ENREKANG - R Wulan; Eka Dewi Kartika; Rezki Amaliah; Fadli Yasser Arafat Juanda; Nurhikmah (Program Studi Hukum Universitas Sulawesi Barat, 2024)
The research aims to find out the legal position regarding users of private vehicles used as public transportation or goods transportation in Law Number 22 of 2009 concerning Road Traffic and Transportation. The type of research in this writing uses normative - empirical legal research. According to Abdulkadir Muhammad, what is meant by normative - empirical legal research applied law research) is research that uses normative - empirical legal case studies in the form of legal behavioral products. The results of this research conclude that the position of private transportation as public transportation is a violation of misuse of Law Number 22 of 2009 concerning traffic and road transportation. This violation can be subject to criminal administrative sanctions. However, many people in Enrekang Regency still use private vehicles as public transportation. This is due to the lack of knowledge about the differences between public transportation and private transportation. However, the law enforcement carried out by the police regarding private cars being used as public transportation is not enforced because there are still many people who do it and are not punished.